Sustainability of Water Resources of Azerbaijan, Future Prospects and Problems - Pasha, Natig H.; Zengin, Eyüp; Baylarli, Afgan T. (Journal of Management, Economics, and Industrial Organization, 2023)
In the integrated management of water resources, factors such as social status, economic development of the region, and energy costs should be taken into account while maintaining the principles of sustainability, efficiency, and priority. Sustainability in the use of water resources is the principle of transferring resources to future generations under the best conditions without causing changes in the ecosystem. Rationality and sustainability in the use of water resources can be achieved through cross-sectoral integrated planning and management of water users. The protection and sustainability of water resources is a key principle in the integrated management of water resources. This study examines the unplanned and wasteful use of water resources leading to disruption of many freshwater ecosystems, the likelihood of creation of more pressure by expected food and energy demand with rapid population growth on hydro systems, and the sustainable and better management of water resources being one of the most important topics of the 21st century. The research method is based on the analysis of technical and legal documents and reports of the State Statistics Committee on water management data in Azerbaijan, compiled by regulatory bodies operating on water management.